PENDAPAT AL-SYAFI’I TENTANG FASAKH PERKAWINAN KARENA SUAMI TIDAK MAMPU MEMBERI NAFKAH - Mas'ud, Muhamad; Suhaeni, Suhaeni; Rosbandi, Rosbandi (Universitas Islam Syekh-Yusuf, 2022)
Marriage is a contract that gives rise to the ability to associate between men and women in the demands of the human instinct in life, and makes for both parties reciprocally rights and obligations. But in certain circumstances there are things that result in the breaking of the marriage bond. The breakup of the marriage exists in several forms, one of the forms being fasakh. The breakup of the marriage with this fasakh brought the consequence of not eliminating the obligation to provide for his children. Point of issue What are the reasons al-Shafi'i argues that a wife has the right to file a fasakh suit for a husband who is unable to provide a living, What is the legal basis used by al-Shafi'i, that a wife has the right to file a fasakh suit for a husband who is unable to provide a living, What is the Istinbath al-Ahkam method used by al-Shafi'i. The purpose of the study is to find out al-Shafi'i's reasons that a wife has the right to file a marriage fasakh lawsuit for a husband who is unable to provide a living, to know the basis of hu kum used by al-Shafi'i about the marriage fasakh lawsuit for a husband who is unable to provide a living, to find out the Istinbath Al-Ahkam method used by al-Shafi'i. The research method used is the content analysis method because it intends to express al-Shafi'i's opinion contained in his books. The data sources in this study were obtained from primary data sources and secondary data sources. The primary source of data is al-Shafi'i's book